The Way of the Táltos: A Critical Reassessment of a Religious-Magical Specialist Pota taltosov: Kritično ovrednotenje posvečenca v religijo in magijo - Kürti, László (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">For a long time, Hungarian scholars debated the origin and structure of Hungarian folk religion and folk beliefs. This article considers the relevance of shamanism to Hungarian folk belief, especially the complex surrounding the táltos. This Hungarian magical practitioner reveals connections both with historical magical specialists and with recent ethnographical materials. There are, however, important questions that must be answered: for example, how does the táltos figure in Hungarian religion, magic, and folkloric practices appear? What are the specific connections with neighbouring South Slavic, Romanian and western magical practices? And, finally, how does the táltos belief relate to linguistic, symbolic and bodily expression in Hungarian traditional culture? This article attempts to answer some of these questions by focusing on body symbolism, the mythical horse symbolism, and possible altered states of consciousness phenomena.